Inattention, Working Memory, and Goal Neglect in a Community Sample - Elisa, Rebecca N.; Balaguer-Ballester, Emili; Parris, Benjamin A. (Frontiers in Psychology, 2016)
Executive function deficits have been linked to attention deficit hyperactivity disorder (ADHD), but it has been theorised that the symptom inattention is specifically related to problems with complex verbal working memory. Using the Conners Adult ADHD rating scale, adults aged 18-35 were assessed for ADHD symptoms, and completed tasks designed to tap verbal and spatial aspects of WM (Experiment 1). Results showed that high inattention predicted poor performance on both simple and complex verbal working memory measures. Results relating to spatial working memory were inconclusive. In a follow up experiment based on the theory that those with inattention have problems receiving verbal instructions, a measure of goal neglect assessing integration of information into a task model in working memory was employed (Experiment 2). Results showed that high inattention uniquely predicted performance on this task, representing the first reported association between inattention and the phenomenon of goal neglect. The results from both experiments lend support to the WM theory of inattention.